-9/3 + 4
-3 + 4 = 1
The answer to the question
Y = 2x + 1
y = 2(-1) + 1
y= -2 + 1
y= -1
Answer:
-82/3
Step-by-step explanation:
first divide -8/9 by -2/3
-8/9 ➗ -2/3 =-8/9*3/-2 =4/3
multiply 4/3 by -41/2
4/3*-41/2 = -82/3
It means not to get too invested in details or to become so invested in something that you can’t focus on anything else.
Answer:
A) -9/2
B) 9/4
C) -9/2, same as A)
Step-by-step explanation:
We are given that
. We use the properties of integrals to write the new integrals in terms of I.
A)
. We have used that ∫cf dx=c∫f dx.
B)
. Here we used that reversing the limits of integration changes the sign of the integral.
C) It's the same integral in A)